Is there a Homogeneous Causality Pattern between Oil Prices and Currencies of Oil Importers and Exporters? - Joscha Beckmann; Robert Czudaj (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
Although the link between oil prices and dollar exchange rates has been frequently analyzed, a clear distinction between prices and nominal exchange rate dynamics and a clarification of the issue of causality has not been provided. In addition, previous studies have mostly neglected nonlinearities which for example may stem from exogenous oil price shocks. Using monthly data for various oil-exporting and oil-importing countries, this study contributes to the clarification of those issues. We discriminate between long-run and time-varying short-run dynamics, using a Markov-switching vector error correction model. In terms of causality, the results differ between the economies under observation but suggest that the most important causality runs from exchange rates to oil prices, with a depreciation of the dollar triggering an increase in oil prices. On the other hand, changes in nominal oil prices are responsible for ambiguous real exchange rate effects mostly through the price differential and partly also through a direct influence on the nominal exchange rate. Overall, the fact that the adjustment pattern frequently differs between regimes underlines the fact that the relationships are subject to changes over time, suggesting that nonlinearities are an important issue when analyzing oil prices and exchange rates. – – Obwohl Interdependenzen zwischen Ölpreisen und Wechselkursen gegenüber dem Dollar ein populäres Forschungsfeld darstellen, hat die bisherige Literatur weder die Frage der Kausalität final geklärt, noch eine klare Unterscheidung zwischen Preis-und nominalen Wechselkursdynamiken geliefert. Darüber hinaus haben früheren Studien nichtlineare Kausalmuster, die beispielsweise auf exogene Ölpreisschocks zurückzuführen sind, vernachlässigt. Basierend auf monatlichen Daten für verschiedene Ölexporteure und Ölimporteure analysiert die vorliegende Studie diese Forschungsfragen in einem Zeitreihenkontext. Basierend auf einem Markov-Switching-Fehlerkorrekturmodel wird zwischen kurz-und langfristigen Dynamiken unterschieden. Die empirischen Ergebnisse verdeutlichen zunächst, dass die Ergebnisse weder für Ölimporteure noch für Ölexporteure komplett homogen sind. Hinsichtlich der Kausalität zeigt sich, dass eine Abwertung des Dollar oftmals mit einem Anstieg des Ölpreises einhergeht, wohingegen Veränderungen des nominalen Ölpreises über Preis-und nominale Wechselkurseffekte ambivalente reale Wechselkursreaktionen hervorrufen. Die Analyse der Kurzfristdynamiken legt nahe, dass regimeanhängige Anpassungsdynamiken auftreten und Nichtlinearitäten ein wichtiges Charakteristikum des Zusammenhangs von Ölpreisen und Wechselkursen sind.
Keywords: C32; E31; F31; G15; 330; Bayesian econometrics; cointegration; exchange rates; Markov-switching model; oil prices; oil-importing and oil-exporting countries